Sustainable Agriculture: Theories, Methods, Practices and Policies (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The progress of science and technology and intensive land usage have promoted the rapid development of modern agriculture. Meanwhile, however, modern agriculture has caused global ecological and environmental problems due to its consumption of large amounts of resources and energy. To meet these challenges, we must rethink the theories, policies, models, and technologies involved in modern agricultural development, which includes new concepts and methods of agriculture: for example, organic agriculture, compound agriculture, circular agriculture, and ecological agriculture. There is a growing awareness that the development of sustainable agriculture should not only increase yields to meet people's demands, but also should improve product quality and promote multi-functioning of the agricultural ecosystem. Although the study and practices of sustainable agriculture have achieved remarkable results in the past 40 years, the development of the social economy and current challenges of world agriculture require significant consideration for the future of agriculture. Summarizing available knowledge and lessons, analyzing associated problems, and mapping out future developments will help in promoting the practice and policy of sustainable agriculture, as well as in innovating sustainable agricultural theory and methods. This reprint includes 16 articles that focus on theoretical methods, policies, and practical experience related to sustainable agricultural development, aiming to contribute to the sustainable development of agriculture and food security.